Hubungan Antara Perilaku Caring Perawat Terhadap Kepuasan Pasien Saat Pandemi Covid-19 di Ruang Perawatan Salah Satu Rumah Sakit Swasta di Yogyakarta - Dyah Lestari, Martina; Sri Oktri Hastuti, Agustina; Maura Harjanti CB, Sr. Therese (I Care Jurnal Keperawatan STIKes Panti Rapih, 2021)
ABSTRCT Background: Patient satisfaction is one of the factors used to evaluate the quality of service in the hospital, and is one of the factors determining the image of a health service institution. Nursing service satisfaction is obtained from consumer assessments regarding the quality and performance of the benefits received from products or services. Quality nursing services can be realized through the provision of nursing care based on the caring behavior of nurses. Caring behavior must always be carried out by nurses in all conditions, even during the current COVID-19 pandemic situation. In the preliminary study conducted, Elisabeth 4's inpatient room was the room that experienced the lowest decrease in customer satisfaction. Purpose: The purpose of this study was to determine the relationship between nurse caring behavior and patient satisfaction during the COVID-19 pandemic in Elisabeth 4 Hospital's inpatient room. Panti Rapih, Yogyakarta. Methods: This type of research is a descriptive correlation. This research is a quantitative study with a cross sectional design. Using non probability sample techniques, purposive sample. The sample used was 37 respondents. Data collection techniques using a questionnaire that is given directly to the respondent in Januari 2021 sampai Februari 2021. Results: The highest nurse caring behavior was in the good category, 83.8% of the total respondents. The highest level of satisfaction is "Satisfied" 54.1% of the total respondents and "Very Satisfied" as much as 43.2% of the total respondents. Based on the results of the Spearman rho test, P value 0.007 is, this means that there is a significant relationship between nurse caring behavior and the level of patient satisfaction. The Correlation Coefficient value is positive, which indicates that there is a strong relationship between nurse caring behavior and the level of patient satisfaction. Conclusion: There is a significant relationship between nurse caring behavior and patient satisfaction. The direction of the positive correlation shows that the higher the nurse's caring behavior, the higher the patient's satisfaction in nursing services. Suggestion: It is necessary for nurses to increase knowledge, attitudes and skills especially when carrying out their role as executor of professional nursing actions. Panti Rapih Hospital management should continue to encourage the spirit of caring behaviour during the COVID-19 pandemic, by improving the physical, mental and spiritual health of nurses so that nurses can provide professional nursing services.